Molecular Characterization of Infectious Bursal Diseases Virus VP2 Gene Fragments Obtained from Commercial Broiler Farms in Central Java and The Yogyakarta Special Region Province - Damairia, Bernike Anggun; Putri, Khrisdiana; Wibowo, Michael Haryadi (Bogor Agricultural University, Indonesia, 2024)
Infectious Bursal Disease (IBD) is an infectious and immunosuppressive disease primarily affecting young chickens. Despite stringent biosecurity and vaccination for control measures, the effective management of IBD remains challenging. The disparity in observed clinical symptoms in the field infections further complicates matters for breeders. The study aims to perform molecular characterization of VP2 gene fragments to identify the latest genotype of field IBD viruses. Twenty-two samples of bursa of Fabricius were collected from broilers suspected of IBD in commercial farms located in Central Java and The Yogyakarta Special Region from 2021 to 2022. Viral RNA was extracted from these samples, and after amplification, a 743 bp PCR product was obtained and subjected to sequencing. The obtained sequences were analyzed in Mega X for multiple alignments, amino acid prediction, homology, and phylogenetic tree construction. Lesion, i.e., Bursa of Fabricius enlargement, oedema, swelling of plica bursa, gelatinous mass, hemorrhage, atrophy, and thigh muscles petechiae to hemorrhage, were considered indicative of IBD. Out of 22 samples tested by RT-PCR, 19 were positive, and 13 samples were selected for sequencing. All sequenced samples belonged to Genogroup A3, specifically the very virulent IBD (vvIBD) strain.